INVENTARISASI GULMA PADA PERKEBUNAN COKELAT DESA PAJAR BULAN KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Dewi, Rosanti (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Research of inventarisation of  weeds in caccao crop was conducted on Februari till Maret  2012 at Pajar Bulan  village in Lahat Recency, Sumatera Selatan Province, to saw diversity weed species.  This research utilited the direct  observation with    Plot Analisys Methods in 1 hectares area during one week.  The result showed   8 species are Euphorbia hirta (Patikan kebo),   Centella asiatica (kaki kuda),  Ageratum conyzoides (bandotan), Synedrella nodiflora (jotang kuda), Crassocephalum crepidioides (sintrong), Fimbristylis annua (teki), Cyperus rotundus (teki ladang) dan   Caladium sp (keladi), from 1 division,  2 class,  5  order,  5 family, 8 genera. Key words : cacao crop, weeds, inventarisation